Evaluating the costs of cholera illness and cost-effectiveness of a single dose oral vaccination campaign in Lusaka, Zambia - Tembo, Tannia (PLoS One, 2019)
INTRODUCTION: In 2016, for the very first time, the Ministry of Health in Zambia implemented a reactive outbreak response to control the spread of cholera and vaccinated at-risk populations with a single dose of Shancol—an oral cholera vaccine (OCV). This study aimed to assess the costs of cholera illness and determine the cost-effectiveness of the 2016 vaccination campaign. METHODOLOGY: From April to June 2017, we conducted a retrospective cost and cost-effectiveness analysis in three peri-urban areas of Lusaka. To estimate costs of illness from a household perspective, a systematic random sample of 189 in-patients confirmed with V. cholera were identified from Cholera Treatment Centre registers and interviewed for out-of-pocket costs. Vaccine delivery and health systems costs were extracted from financial records at the District Health Office and health facilities. The cost of cholera treatment was derived by multiplying the subsidized cost of drugs by the quantity administered to patients during hospitalisation. The cost-effectiveness analysis measured incremental cost-effectiveness ratio—cost per case averted, cost per life saved and cost per DALY averted—for a single dose OCV. RESULTS: The mean cost per administered vaccine was US$1.72. Treatment costs per hospitalized episode were US$14.49–US$18.03 for patients ≤15 years old and US$17.66–US$35.16 for older patients. Whereas households incurred costs on non-medical items such as communication, beverages, food and transport during illness, a large proportion of medical costs were borne by the health system. Assuming vaccine effectiveness of 88.9% and 63%, a life expectancy of 62 years and Gross Domestic Product (GDP) per capita of US$1,500, the costs per case averted were estimated US$369–US$532. Costs per life year saved ranged from US$18,515–US$27,976. The total cost per DALY averted was estimated between US$698–US$1,006 for patients ≤15 years old and US$666–US$1,000 for older patients. CONCLUSION: Our study determined that reactive vaccination campaign with a single dose of Shancol for cholera control in densely populated areas of Lusaka was cost-effective.